Death penalty: problems with retributive justice approach - Vondráková, Jana (Univerzita Pardubice, 2024)
This thesis deals with an issue of capital punishment, namely, but not exclusively, from the retributive perspective. The general aim is to prove that capital punishment has no place in contemporary democracies. To reach the aim, topic is analyzed first from the perspective of moral philosophy, to understand, why capital punishment is inappropriate punishment from both moral and political perspective.
Trest smrti: problematika retributivního přístupu ke spravedlnosti
Keywords: trest smrti; teorie trestu; etika; politická filozofie; capital punishment; theory of punishment; ethics; political philosophy